(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2021)
This study was conducted to determine the level of utilization of the reading motivation approaches by public elementary school teachers in Cluster III of Alaminos City Division during the school year 2019 - 2020. Specifically, it delved on determining the profile of the respondents, the level of utilization of teachers on the reading motivation approaches, and the level of seriousness of the problems encountered by the teachers in utilizing the reading motivation approaches. Likewise, it determined the significance of the difference of the level of utilization of the public elementary schools on the reading motivation approaches across their profile variables. Moreover, it determined if the level of seriousness of the problems encountered in utilizing the reading motivation approaches differ significantly across the respondent-teachers’ profile variables. The study made use of the descriptive-survey method of research with the FivePoint Likert Questionnaire as the main tool used in gathering pertinent data to this study.